EFEKTIFITAS SENAM ERGONOMIS TERHADAP PENURUNAN KADAR ASAM URAT PADA LANJUT USIA DENGAN ARTHRITIS GOUT - Abdul Thalib; Daniawan Bugis; Kreshas J.A Noija (Pasapua Health Journal, 2020)
Introduction: Gouty arthritis is a disease caused by disturbances of purine metabolism characterized by hyperuremia and repeated attacks of acute synovitis. This disorder is associated with the accumulation of monohydrate monosodium urate crystals and at a more advanced stage, joint cartilage degeneration occurs. Method: This research is a non-equivalent control group design study with the aim of knowing the effectiveness of ergonomic exercises on reducing uric acid levels in elderly people with arthritis gout. The sampling technique used is non-probability sampling with purposive sampling technique, quasy experimental design or judgment sampling, namely the sampling method is carried out by selecting samples that meet the research criteria for 1 week, so that the number of samples is fulfilled, namely as many as 20 people, by dividing 10 people into groups intervention and 10 control group. Wilcoxon Signed Ranks Test on pre-test and post-test uric acid levels in the intervention group. Result : The intervention group obtained a p-value of 0.002 or p <0.05, which means that there was a significant effect before and after giving ergonomic exercises. Conclusion: that ergonomic exercise has an effect on reducing uric acid levels in the blood in the elderly with gouty arthritis in the Work Area of the Hila Health Center, Leihitu district. Kab. Central Moluccas. Thus, it is hoped that people, especially gout arthritis sufferers, should do ergonomic exercises independently and regularly, besides that it is also necessary to regulate a healthy lifestyle in order to prevent more severe complications.